Analysis of the Influence of Organizational Management and Student Leadership in Increasing the Independence of Islamic Boarding Schools - Irma Herliza Rizki; Putri Mauliza; Muammar Rinaldi; Emmy Ermina (Outline Publisher, 2024)
The Organizational Management and Leadership Workshop for Students to Improve the Independence of Islamic Boarding Schools aims to improve the managerial and leadership skills of students in managing Islamic boarding schools. Through various methods such as simulations, group discussions, and role plays, workshop participants gain a deeper understanding of financial management, activity planning, and efficient and effective decision-making. In addition, participants are also trained in communication, team collaboration, and the preparation of action plans to improve the independence of Islamic boarding schools, especially in terms of economy. This activity also emphasizes the importance of the active role of students in every decision-making process and management of Islamic boarding schools. Although challenges in implementing the material still exist, especially related to changes in the organizational culture of more traditional Islamic boarding schools, this workshop provides a strong foundation for the development of more independent Islamic boarding schools. To ensure sustainability, continued mentoring and collaboration with external parties such as the business world and government are needed. Overall, this workshop helps create skilled Islamic boarding school leaders, not only in the fields of religion and education, but also in professional management and leadership.